Identifying the drivers of sustainable rural growth and poverty reduction in Honduras - Jansen, Hans G. P.; Siegel, Paul B.; Pichon, Francisco (International Food Policy Research Institute, 2005)
The overall objective of this paper is to develop an appropriate conceptual and analytical framework to better understand how prospects for growth and poverty reduction can be stimulated in rural Honduras. We employ complementary quantitative and qualitative methods of analysis, driven by an asset-base approach. Emphasis on assets is appropriate given high inequalities in the distribution of productive assets among households and geographical areas in Honduras. Such inequalities are likely to constrain how the poor share in the benefits of growth, even under appropriate policy regimes. We focus on household assets (broadly defined to include natural, physical, human, financial, social and locational assets) and their combinations necessary to take advantage of economic opportunities. We examine the relative contributions of these assets, and identify the combinations of productive, social, and location-specific assets that matter most to raise incomes and take advantage of prospects for poverty-reducing growth. Factor and cluster analysis techniques are used to identify and group different livelihood strategies; and econometric analysis is used to investigate the determinants of different livelihood strategies and the major factors that impact on income. Spatial analysis, community livelihood studies and project stocktakings are brought in to complement some of the more quantitative household survey data used. Our conclusions and recommendations are mainly focused on hillsides and hillside areas since the majority of the available data is for these areas.-- Authors' Abstract